Death by Data - Andrew Fitzgerald (Media Theory)
Computational state violence has developed through the broader political economy of datafication, where increasing dimensions of life are “made productive” via the intensification of enclosure, data capture, and analysis for recursive operationalization. Through a Marxist conceptualization of abstraction, this article analyzes the U.S.’s use of metadata and geolocation algorithms for targeted killings, and the broader “platformization of the military” including Israel’s AI-powered bombing campaigns. It examines two interrelated aspects of the rhetoric legitimating this lethal labor, which compound abstraction and ethico-political mystification: first, “accountability” frameworks embracing illusions of human oversight for systems operating beyond human cognition and accelerating deadly action; second, the framing of the technology itself as both problem and solution, normalizing fallibility and the unknowability of lethal outcomes in the factory-like production of mass violence. Capitalism’s data-driven expansion extends responsibility for computational state violence to commercial users of datafied systems, obliging mass action to halt the scaling of these systems’ atrocities.